To be silent ... would be criminal: the antislavery influence and writings of Anthony Benezet - Brendlinger, Irv A. (Revitalization: explorations in world Christian movements, 2007)
Introduction -- Benjamin Lay and early protesters -- Benezet's life, an overview -- Benezet's antislavery writing -- Benezet's most explicit influence -- Others influenced by Benezet -- In response to the closing of the life -- Letters -- Tracts